2015
DOI: 10.1590/1516-1439.341714
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Galvanized Steel Under Different Soil Moisture Contents

Abstract: Galvanized steel has been widely applied in different applications and the industry significantly increased its production in recent years. Some galvanized structures can be completely or partially buried, such as transmission tower footings. The corrosion of these metallic structures is related to the soil chemical and physicochemical properties, which define the aggressiveness of the environment. To assess the effect of the soil moisture on galvanized steel corrosion, a comparative study was carried out. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 4 publications
2
15
0
1
Order By: Relevance
“…In 1979, research showed a direct correlation between the mass loss in pipework and the moisture content of soils [48]. In 2015, the results of a study to evaluate the effect of soil moisture on corrosion confirmed its important influence on corrosion rates [51]. The reason for this is that liquid water represents the essential electrolyte for electrochemical corrosion reactions.…”
Section: Presence Of Watermentioning
confidence: 99%
“…In 1979, research showed a direct correlation between the mass loss in pipework and the moisture content of soils [48]. In 2015, the results of a study to evaluate the effect of soil moisture on corrosion confirmed its important influence on corrosion rates [51]. The reason for this is that liquid water represents the essential electrolyte for electrochemical corrosion reactions.…”
Section: Presence Of Watermentioning
confidence: 99%
“…Otherwise, a corrosion attack would tend to follow localized pits [16]. As reported by Pereira et al, soil moisture less than 20% is associated with high soil resistivity, which decreases until reaching minimum resistivity by adding water [21].…”
Section: Moisture Contentmentioning
confidence: 79%
“…The moisture content of the studied soil ranges from 14.33% to 29.09% characteristic of moist soils with fair drainage [6]. Low moisture content generally suggests high resistivity and low soil corrosivity [8,23,24]. An increase in soil moisture content lowers soil resistivity and favours corrosion of metallic structures.…”
Section: Resultsmentioning
confidence: 99%